Profitability as a Moderator of Leverage and Firm Size on Tax Avoidance: Empirical Study at Indonesia Construction Companies - Anjar Indriyanti; Ibram Pinondang Dalimunthe (eCo-Fin, 2023)
This study aims to analyze the effect of profitability as moderating leverage and firm size on tax avoidance. The independent variables are leverage, firm size, the dependent variable is tax avoidance and profitability as a moderator. This research is quantitative data, with sample selection using purposive sampling. Sample study in this research are construction companies listed on the Indonesia Stock Exchange (IDX) in 2015-2020. Analysis method in this study processes using e-views version 9. The results of this study indicate that leverage and firm size have a significant effect on tax avoidance. The study also give evidence that profitability weakens the relationship between leverage and tax avoidance and profitability weakens the relationship between firm size and tax avoidance